2014
DOI: 10.1080/17470218.2013.837940
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Performance in Discrete and Continuous Comparison Tasks

Abstract: The approximate number system (ANS) theory suggests that all magnitudes, discrete (i.e., number of items) or continuous (i.e., size, density, etc.), are processed by a shared system and comply with Weber's law. The current study reexamined this notion by comparing performance in discrete (comparing numerosities of dot arrays) and continuous (comparisons of area of squares) tasks. We found that: (a) threshold of discrimination was higher for continuous than for discrete comparisons; (b) while performance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
84
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 29 publications
(63 reference statements)
9
84
1
3
Order By: Relevance
“…Piazza et al suggested the results obtained under these controlled conditions should be attributed to the processing of numerosity and not to continuous magnitudes. However, this method was criticized on several grounds (Gebuis & Reynvoet, 2011;Leibovich & Henik, 2013, 2014Leibovich, Henik, & Salti, 2015). Mainly, disassociating a single continuous magnitude ignores the possibility that participants might rely on several continuous magnitudes or even switch between them (see Leibovich & Henik, 2014).…”
Section: Methods Of Controlling For Continuous Magnitudes In Numericamentioning
confidence: 99%
See 2 more Smart Citations
“…Piazza et al suggested the results obtained under these controlled conditions should be attributed to the processing of numerosity and not to continuous magnitudes. However, this method was criticized on several grounds (Gebuis & Reynvoet, 2011;Leibovich & Henik, 2013, 2014Leibovich, Henik, & Salti, 2015). Mainly, disassociating a single continuous magnitude ignores the possibility that participants might rely on several continuous magnitudes or even switch between them (see Leibovich & Henik, 2014).…”
Section: Methods Of Controlling For Continuous Magnitudes In Numericamentioning
confidence: 99%
“…However, this method was criticized on several grounds (Gebuis & Reynvoet, 2011;Leibovich & Henik, 2013, 2014Leibovich, Henik, & Salti, 2015). Mainly, disassociating a single continuous magnitude ignores the possibility that participants might rely on several continuous magnitudes or even switch between them (see Leibovich & Henik, 2014). Reynvoet (2011, 2012b) created a code that manipulates congruency between numerosity and one or several continuous magnitudes.…”
Section: Methods Of Controlling For Continuous Magnitudes In Numericamentioning
confidence: 99%
See 1 more Smart Citation
“…These visual properties are continuous, noncountable dimensions such as density, total surface area, and so forth (hereafter, we will refer to all continuous properties as "nonnumerical magnitudes"). Therefore, it is also possible that, when you are deciding which line to join in the supermarket, you are using nonnumerical magnitudes or a combination of numerical and nonnumerical magnitudes (Leibovich & Henik, 2013;Henik, Leibovich, Naparstek, Diesendruck, & Rubinsten, 2012;Mix et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is evidence that both numerical (Cantlon, Libertus, et al, 2009;Nieder & Dehaene, 2009) and nonnumerical (e.g., Leibovich & Henik, 2013Gebuis & Reynvoet, 2011;Mix et al, 2002;Clearfield & Mix, 1999) magnitudes are being processed automatically when comparing numerical magnitudes. That is, for example, when deciding which of two dot arrays is numerically larger, the task-irrelevant nonnumerical magnitudes (e.g., array, density) influence RTs and accuracy although they are not relevant to the task.…”
Section: Introductionmentioning
confidence: 99%